Paroxysmal Symptoms As the First Manifestation of Multiple Sclerosis Mimicking a Transient Ischemic Attack: A Report of Two Cases - Zhang, Yao; Fan, Siyuan; Han, Fei; Xu, Yan (Frontiers in Neurology, 2017)
Paroxysmal symptoms are unusual manifestations of multiple sclerosis (MS). When presented as the first clinical manifestation, paroxysmal symptoms may easily be mistaken for transient ischemic attack (TIA). Previously, only two cases of MS have been reported with paroxysmal symptoms and were misdiagnosed as TIA. Here we report two additional cases, focusing on the clinical characteristics of paroxysmal symptoms in MS. Both cases had paroxysmal symptoms as their first manifestation; one presented with transient dizziness, left face numbness, and right limb weakness, and the other presented with episodic lightheadedness, blurred vision, nausea, palpitations, and tremulousness upon standing. Both of the patients’ symptoms were mistaken for TIA at first, based on microembolic signals recorded by transcranial doppler (TCD), but were later correctly diagnosed with MS based on neuroimaging and lumbar puncture. The paroxysmal symptoms responded to carbamazepine and were relieved completely after administration of intravenous methylprednisolone and interferon. Herein we aim to summarize the differences between paroxysmal symptoms seen in MS and TIA, facilitate a timely differential diagnosis, and recommend an early appropriate treatment.